1965
DOI: 10.2134/agronj1965.00021962005700010011x
|View full text |Cite
|
Sign up to set email alerts
|

Barley Production Under Various Nitrogen and Moisture Levels1

Abstract: Synopsis A three‐year barley study with irrigation and nitrogen variables at Yuma, Arizona, demonstrated the importance of investigating components leading to yield such as: plants per unit area, heads per plant, seeds per head, and individual size or weight per seed. Nitrogen rate increased barley yields appreciably, predominantly by increasing heads per plant and seeds per head. Moisture utilization efficiency—pounds of grain per acre‐inch of water—was favored by higher N rates and the drier moisture regimes. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Drainage problems reduce the absorptive capacity of roots and create water stress, thus retarding growth and development (Kramer, 1969). Stanberry and Lowrey ( 1965) have shown that low N availability can be related to decreased development rates in barley. Because poorly drained sites may have had decreased aeration as well as N, both factors could have attributed to slower development.…”
Section: Phenological Stagesmentioning
confidence: 99%
“…Drainage problems reduce the absorptive capacity of roots and create water stress, thus retarding growth and development (Kramer, 1969). Stanberry and Lowrey ( 1965) have shown that low N availability can be related to decreased development rates in barley. Because poorly drained sites may have had decreased aeration as well as N, both factors could have attributed to slower development.…”
Section: Phenological Stagesmentioning
confidence: 99%
“…On the contrary, many researchers have shown that barley responded to relatively high fertilizer levels, whether under irrigated or dry farming conditions. Stanberry and Lowery (1965) showed that barley production was increased with the addition of up to 135 kg.ha ' of N, when they used 1010 mm water, but under limited moisture (470 mm) the response was only up to 65 kg.ha"' of N. On the other hand, Luebs and Laag (1967) pointed out that the yield of barley was reduced when a high amount of nitrogen was used under high water tension. Dwiredi et al (1989) showed that increasing nitrogen up to 80 kg.ha"' increased the number of tillers, spike length and grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…The response of yield components generally varies widely with moisture supply, soil fertility level, and other growth-limiting factors. Schreiber and Stanberry (1965) and Stanberry and Lowrey (1965) reported that barley spikes per plant were increased. by increasing soil moisture during internode elongation with high N rates, especially when N was applied during elongation.…”
mentioning
confidence: 99%